Improving Early Childhood Cognitive Skills Through Geometry Pouch Media - Novriyanti, Intan; Zettira, Zahra (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to improve the cognitive abilities of early childhood through shape and color guessing games using flannel-based geometry pouch media. This media is designed to introduce basic geometry concepts interactively, integrating the principles of learning through play. The research method used is a qualitative study with a literature review approach. The results show that the flannel-based geometry pouch media is effective in enhancing children's cognitive abilities, especially in recognizing shapes and colors, while also creating a fun and interactive learning experience for students. This literature review does not involve direct interaction with research subjects, but rather emphasizes the analysis of reading materials and written information.